The Cost of Government and the Misuse of Public Assets - Prakash, Tej (IMF Working Papers; Working Paper ;, 2000)
This paper deals with efficiency in the public sector. It argues that the habit of relating efficiency to public spending, as is generally done, may give wrong results when, as is often the case, public institutions use public assets (land, buildings, et cetera) without imputing a cost for that use. The paper argues that, because of lack of incentives, governments are often wasteful in their use of publicly held assets. It recommends the creation of 'cadastres' of publicly owned assets that could be used for several purposes including increasing public sector efficiency.